Electro/magnetic superposition effects on diclofenac degradation: Removal performance, kinetics, community structure and synergistic mechanism. (1st January 2022) - Feng, Yan; Li, Zichen; Long, Yingying; Suo, Ning; Wang, Zhongwei; Qiu, Lipin
Abstract: Electric and magnetic fields characterized by high efficiency, low consumption and environment-friendly performance have recently generated interest as a possible measure to enhance the performance of the biological treatment process used to remove refractory organics. Few studies have been carried out to-date regarding the simultaneous application of electric and magnetic fields on biofilm process to degrade diclofenac. In this study, 3DEM-BAF was designed to evaluate the electrio-magnetic superposition effect on diclofenac removal performance, kinetics, community structure and synergistic mechanism. The results show that 3DEM-BAF could significantly increase the average removal rate of diclofenac by 65.30 %, 57.46 %, 9.48 % as compared with that of BAF, 3DM-BAF, 3DE-BAF, respectively. The diclofenac degradation kinetic constants and dehydrogenase activity of 3DEM-BAF were almost 6.72 and 2.53 times higher than those of BAF. Microorganisms of 3DEM-BAF in the Methylophilus and Methyloversatilis genera were distinctively enriched, which was attributed to the screening function of electric field and propagation effect of magnetic field. Moreover, three processes were found to contribute to diclofenac degradation, namely electro-magnetic-adsorption, electro-chemical oxidation and electro-magnetic-biodegradation. Thus, the simultaneous application of electric and magnetic fields on biofilm process was demonstrated to be a promising technique as well as a viable alternative in diclofenac degradation enhancement. Graphical abstract: In order to demonstrate the superposition effect of electric/magnetic field, seven other reactors with identical shape and size were provided with the following specification: BAF, biofilm reactor, no electric or magnetic fields; 3DE-BAF, biofilm reactor, only under a current density of 0.29 mA/cm 2 ; 3DM-BAF, biofilm reactor, only under a magnetic field intensity of 5 mT; 3DR, a reactor without biofilm, no electric or magnetic fields; 3DER, a reactor without biofilm or magnetic field, under a current density of 0.29 mA/cm 2 ; magnetic; 3DMR, a reactor without biofilm or electric field, under a magnetic field intensity of 5 mT; 3DEMR, a reactor without biofilm, under a current density of 0.29 mA/cm 2 and magnetic field intensity of 5 mT. The description of above reactors were shown in Table 1.